Nitrofurantoin inhibits contractions of myometrium isolated from pregnant and nonpregnant rats - Ebru Celik Kavak; Emine Kacar; Salih Burcin Kavak; Ozgur Bulmus (Medicine Science, 2018)
We aimed to investigate the effects of nitrofurantoin, a commonly used antibiotic for urinary tract infections, on spontaneous contractions of rat myometrium isolated from 16-day pregnant and nonpregnant rats. Myometrial strips were suspended in a standard organ bath and after the manifestation of spontaneous contractions under 1 g of resting tension, nitrofurantoin was applied to the organ bath as 50, 250 and 500 µM doses. Amplitude and frequency of contractions were recorded for 20 minutes before and after application of the drug. The bath was washed to remove the drug from the medium after recording the effect of each dose and the contractions were enrolled again to show the reversible effect of the drug. The effects of nitrofurantoin on amplitude (milligrams) and frequency of spontaneous contractions were evaluated. Data were statistically analyzed using the Students t test and p [Med-Science 2018; 7(2.000): 315-8]